Pengaruh Komitmen Manajemen, Fungsi Pengawasan dan Pengetahuan K3 Karyawan terhadap Pengendalian Tindakan Tidak Aman pada Komunitas Pekerja Pertambangan Batubara - Subhan, Ahmad; Hernawan, Ari; Ahmad, Astiti Tenriawaru (Jurnal Kesehatan Komunitas, 2025)
This research uses a mixed-methods approach with a cross-sectional study design conducted in Tapin District, South Kalimantan. The research population includes 4,704 employees of PT A, with a sample of 374 respondents selected using proportionate stratified random sampling. The research instrument is a validated questionnaire that has undergone readability testing, expert validation (Aiken's V ≥0.75), and reliability testing (Cronbach's Alpha 0.884-0.931). Data analysis uses Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0.9 software. The structural model shows moderate-substantial explanatory power (R²=0.593; Q²=0.364). All three hypotheses were accepted with significance p<0.001. OHS Knowledge is the strongest predictor (β=0.331; f²=0.172 medium), followed by Management Commitment (β=0.285; f²=0.075 small) and Supervisory Function (β=0.272; f²=0.062 small). Convergence of quantitative and qualitative findings shows 50.5% of respondents emphasized OHS knowledge as the most influential factor, with 23.8% recommending priority for applicative training. Controlling unsafe actions depends more on individual competency development than organizational factors, consistent with Social Cognitive Theory. These findings have important implications for community health, as improved workplace safety can reduce accident burden on mining workers and their families. Further research is recommended using longitudinal designs to explore the long-term impact of OHS programs on community health, conducting comprehensive cost-benefit analysis, developing family safety programs models, and exploring mediation-moderation mechanisms using multilevel modeling.